2009
DOI: 10.1176/appi.ajp.2009.08121779
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Suicidal Ideation and Depression in Older Primary Care Patients: 24-Month Outcomes of the PROSPECT Study

Abstract: Objective-The PROSPECT Study evaluated the impact of a care management intervention on suicidal ideation and depression in older primary care patients. This is the first report of outcomes over a 2-year period.Method-The subjects (N=599) were older (>=60 years) patients with major or minor depression selected after screening 9,072 randomly identified patients of 20 primary care practices randomly assigned to the PROSPECT intervention or usual care. The intervention consisted of services of 15 trained care mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
271
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 331 publications
(280 citation statements)
references
References 30 publications
4
271
1
4
Order By: Relevance
“…Comprehensive risk assessments which take into account a wide range of demographic and clinical factors (for example, employment, living circumstances, age, gender, history of self-harm or substance misuse, physical health) are an important suicide prevention measure. 2 Patients who express suicidal ideation at their last consultation but who are rated as low risk (6 patients in 18 primary care and 7 patients in secondary care in this study) may be an important group in whom to intervene.…”
Section: Clinical and Research Implicationsmentioning
confidence: 91%
See 1 more Smart Citation
“…Comprehensive risk assessments which take into account a wide range of demographic and clinical factors (for example, employment, living circumstances, age, gender, history of self-harm or substance misuse, physical health) are an important suicide prevention measure. 2 Patients who express suicidal ideation at their last consultation but who are rated as low risk (6 patients in 18 primary care and 7 patients in secondary care in this study) may be an important group in whom to intervene.…”
Section: Clinical and Research Implicationsmentioning
confidence: 91%
“…Similar to previous studies we found that many patients who died (nearly half the sample) had in fact been rated as at low risk when they were last seen by their clinicians. 18 This 'low risk' paradox in patients who go on to die by suicide reflects the problems inherent in predicting low frequency events, but rapidly changing risk, desensitization to high risk situations (particularly in specialist care), and recall bias might also contribute. 18 In primary care, presentation with physical complaints could mask psychological symptoms and lead to a downgrading of risk.…”
Section: Clinical and Research Implicationsmentioning
confidence: 99%
“…[12][13][14][15] These effects are stronger when collaborative care models of depression treatment are used. 16,17 pATIEnT GroUpS AT rISk Years of research on suicide show those with current psychiatric illness are the most common group dying by sui-…”
Section: Importance To Primary Carementioning
confidence: 99%
“…They show promise in not only decreasing suicidal behavior 16 but also increasing overall levels of combined treatment with pharmacotherapy and psychotherapy plus faster time to remission vs treatment as usual. 16,42 For example, the Prevention of Suicide in Primary Care Elderly: Collaborative Trial (PROSPECT) was more effective than treatment as usual in reducing suicide risk in patients aged 60 years or older. 16 This finding was present in urban, suburban, and rural practice sites.…”
Section: Education Vs Practice Model Changementioning
confidence: 99%
See 1 more Smart Citation